The Influence of Influencer Credibility on Instagram on Consumer Trust and MS Glow Brand Loyalty - Mulyanto, Kharisma Putri; Hariyanto, Didik (Procedia of Social Sciences and Humanities, 2024)
The research was aimed at seeing the impact of influence influence on instagram belief and loyalty to the consumer media brand Ms. Glow, beauty vlogger social media was becoming a trend and popular culture was being influence thinly by beauty products and brand ambassadors in Indonesia. The study USES a quantitative method. The population in this study is 1400 followers of Ms. Glow's instagram group with a withdrawal of the number of research samples through data collection techniques and a total of 100 users of Ms. Glow's beauty products as a sample of Ms. Glow's research. This research material is a common message Shared online through social media software: a questionnaire and analyzed with simple regression. The findings suggest the use of influence strategies and e-wom in digital marketing. Influence influence diluted to contribute 73.8% to Ms. Glow's product purchase, while the remaining 26.2% were influenced by other variables that were not included in the study. Influence dilution strategies, the brand ambassador of social media, and other supportive strategies are crucial to the decision to buy skin care at Ms. Glow Indonesia. The findings suggest that diluted social media influence influenced buyers' beliefs and brand loyalty in Ms. Glow's purchase decisions.